Construction Claims - Raya Jaber; Tasnim Bany Jaber; Tala Aydi (My University, 2014)
A limited number of construction projects in Palestine which completed within time, and cost, because of the conflicts between parties involve in the construction projects. These conflicts and disputes are known as claims, which include, delay in construction, owner requested changes and acceleration, poor management and many other disputes that may lead into termination of the contract, by knowing causes and how to avoid them claims can be reduced. This research will investigate the causes of construction claims from owner and contractor perspective. Our main objective is to have adequate understanding of the causes of claims which have more frequency and who is responsible for these causes, to avoid or terminate them. Our methodology will involve a systematic process, starts with problem identification and questioner analysis using statistics since adequate number of samples will be determined, then developing ways to avoid or reduce claims in order to achieve the project objectives